Web-Based E-Voting System Implementation with Selection-Count Validation for the Formatur Election of PC IPM Cepu - Ronggo Gusti Anllasosa (MASI Mandiri Edukasi, 2025)
The formatur election at PC IPM Cepu is an important practice of internal democracy within the Muhammadiyah student organization; however, the manual voting process has frequently led to invalid ballots, lengthy vote recaps, and potential recording errors. This study aims to develop a web-based e-voting system that enforces election rules and improves efficiency and data integrity. In this election, voters are required to select exactly nine candidates, which serves as the core validation constraint of the proposed system. The research employs a Research and Development (R&D) method with a prototyping approach, encompassing needs analysis, system design, implementation using the Flask framework with an SQLite database, and system testing. Automatic selection-count validation is implemented on both the client and server sides, along with a double-vote prevention mechanism to ensure voting integrity. System evaluation involved 30 active PC IPM Cepu participants through functional testing, time-efficiency comparison, and a user-satisfaction survey. The results indicate that the system successfully eliminated invalid ballots, achieving 0% input errors, defined as the absence of votes with an incorrect number of selected candidates across all test cases. In addition, the voting and recapitulation process was accelerated by up to 80% compared with the manual method. User satisfaction was measured using a Likert-scale questionnaire, yielding an overall satisfaction rate of 95% (positive responses), derived from aggregated Likert scores. Despite these promising results, this study is limited by its relatively small sample size and its application within a single student organization. Overall, the findings demonstrate that a simple rule-based e-voting system can serve as an effective digitalization model for internal democratic processes in student organizations, enhancing participation and organizational governance efficiency through technology.